2022
DOI: 10.3390/f13060914
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characteristics and Simulation of Enzymatic Lignin Isolated from Chinese Fir and Birch

Abstract: Lignin is one of the main components of the plant cell wall, and the thermal properties of in situ biomass lignin are crucial for the multi-scale modeling of biomass properties and the thermodynamic modeling of lignin. In this study, high yields of double enzymatic lignin (DEL) were successfully isolated from softwood Chinese fir (Cunninghamia lanceolate (Lamb.) Hook.) and hardwood white birch (Betula platyphylla Suk.) to represent the in situ wood lignin. Their thermal properties, including specific heat capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Thus, pLS showed slightly higher heat capacity than LS. Generally, the c P value for the pLS granulate is in accordance with the literature. , …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, pLS showed slightly higher heat capacity than LS. Generally, the c P value for the pLS granulate is in accordance with the literature. , …”
Section: Resultssupporting
confidence: 85%
“…Generally, the c P value for the pLS granulate is in accordance with the literature. 77,78 The polymerized material becomes insoluble in water, which makes it promising for various applications. However, as it turned out, it is also very resistant to organic solvents, hampering further characterization of the polymers.…”
Section: Physicochemical Properties Of Ls Polymersmentioning
confidence: 99%
“…The scanning electron microscope (SEM) comparison of the surface and middle parts (Figure 5) revealed that the surface cell wall was compressed and deformed, while the middle cell wall was almost intact and not compressed. Wang's periodic hot pressing densification SEM images of Chinese fir showed that the early and late wood cell walls and wood rays experienced varying degrees of deformation and distortion [25], indicating that traditional physical compression compressed the entire plate and significantly reduced the volume. The profile density distribution in our study (Figure 4) showed that the surface density was significantly higher than the middle density, demonstrating a high outside and low inside' density distribution resulting from the formation of calcium carbonate that increased the test material's density.…”
Section: Bending Performancementioning
confidence: 99%
“…Active free radicals containing benzene rings are formed, and these can easily react with other molecules or free radicals to generate macromolecules with more stable structures, eventually forming biochar at higher temperatures ( Chen et al, 2022 ). These conclusions were drawn from studies on thermal properties, including thermal stability, and thermal degradation kinetics of lignin ( Wang et al, 2022 ). The pyrolysis process of lignin is dominated by the condensation reaction and degradation and rearranging of smaller structural units within it.…”
Section: Introductionmentioning
confidence: 99%